1995
DOI: 10.1210/mend.9.8.7476996
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase A subunit messenger RNA stability is synergistically regulated via the protein kinase A and C signal transduction pathways.

Abstract: We have identified and studied a posttranscriptional mechanism of lactate dehydrogenase A (LDH) subunit gene expression at the level of mRNA stability. Using the well differentiated rat C6 glioma cell line as a model system, the effects of activators of the protein kinase A and C pathways on the half-life of LDH A mRNA were measured by two independent methods: 1) by the RNA synthesis inhibitor-chase method using actinomycin D, and 2) by analysis of decay of LDH A [3H]mRNA in [3H]uridine-labeled cells. By each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…Although it is known that increased levels of either cAMP or phorbol ester are sufficient signals for increased LDH-A mRNA stability, the molecular mechanisms mediating the effects of cAMP or phorbol ester on mRNA stability have not been defined in detail. Based on our previous data (4, 12), we suggested that sequences within the non-coding regions of LDH-A mRNA together with protein kinase-regulated RNA-binding phosphoprotein(s) may play a pivotal role in determining the basal and regulated stability of mRNA (12,22).In the present study, we have chosen to identify putative cis-regulatory domains within the 3Ј-UTR of LDH-A mRNA that are involved in protein kinases A-mediated mRNA stability regulation. Our initial approach was to express transfected chimeric ␤-globin/ldh 3Ј-UTR constructs and to evaluate the functional effects of protein kinase A on chimeric mRNA stability.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Although it is known that increased levels of either cAMP or phorbol ester are sufficient signals for increased LDH-A mRNA stability, the molecular mechanisms mediating the effects of cAMP or phorbol ester on mRNA stability have not been defined in detail. Based on our previous data (4, 12), we suggested that sequences within the non-coding regions of LDH-A mRNA together with protein kinase-regulated RNA-binding phosphoprotein(s) may play a pivotal role in determining the basal and regulated stability of mRNA (12,22).In the present study, we have chosen to identify putative cis-regulatory domains within the 3Ј-UTR of LDH-A mRNA that are involved in protein kinases A-mediated mRNA stability regulation. Our initial approach was to express transfected chimeric ␤-globin/ldh 3Ј-UTR constructs and to evaluate the functional effects of protein kinase A on chimeric mRNA stability.…”
mentioning
confidence: 95%
“…Although it is known that increased levels of either cAMP or phorbol ester are sufficient signals for increased LDH-A mRNA stability, the molecular mechanisms mediating the effects of cAMP or phorbol ester on mRNA stability have not been defined in detail. Based on our previous data (4,12), we suggested that sequences within the non-coding regions of LDH-A mRNA together with protein kinase-regulated RNA-binding phosphoprotein(s) may play a pivotal role in determining the basal and regulated stability of mRNA (12,22).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The intracellular level of LDH-A mRNA, however, does not entirely reflect the effector agentinduced increased rate of gene transcription (1), implying that its steady-state level is concomitantly regulated by the ability of cells to modulate LDH-A mRNA stability. Indeed, the relatively short half-life LDH-A mRNA (t1 ⁄2 Ϸ 55 min) increases markedly in response to activators of the PKA signal transduction pathway (1,4,6,7). As a consequence, the cellular isoenzyme pattern is shifted in favor of LDH-5 altering the aerobic/ anaerobic metabolic status of cells.…”
mentioning
confidence: 99%
“…Increments in LDH A mRNA levels may be related to increased transcription of ldh a gene. However, considering that Huang et al (1995) have shown that pkC -a signal transduction pathway that may be utilized by bFGF -plays an active functional role in regulating LDH A mRNA stability in rat C6 glioma cells, an mRNA stabilizing mechanism cannot be ruled out. Thus, the possibility exists that, in rat Sertoli cells, bFGF controls the expression of the LDH subunit A at a transcriptional and/or post-transcriptional level.…”
Section: Discussionmentioning
confidence: 99%